EVALUASI USABILITY LINE PADA MAHASISWA ILMU POLITIK UIN JAKARTA MENGGUNAKAN NIELSEN’S ATRIBBUTES OF USABILITY - Achmad Nur Sholeh; Denina Nastiti Putri Amani (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
This study aims to evaluate the usability level of the LINE application by involving UIN Jakarta Political Science students class of 2022 as respondents. The survey method used in this research is a quantitative approach that collects information through a Nielsen survey. The survey evaluated five main usability attributes: learnability, efficiency, memorability, errors, and satisfaction. The results showed that the majority of respondents gave scores above 4 for each attribute on a scale of 1 to 5, indicating that most respondents agreed that the LINE app meets the usability guidelines. The LINE app proved to support students' academic and social activities in an effective and user-friendly manner. Additional evaluations also confirmed that LINE apps positively contribute to interaction and communication among university students. The findings are expected to make important contributions to app developers, particularly in the aspects of administration and further development. The feedback from this survey enables app engineers to continuously refine and improve the features of the LINE app to better suit users' needs. This study concludes that the LINE app has a high level of usability and is able to provide a satisfying user experience, thus supporting effectiveness in students' academic and social activities.